Transformation of char structure and alkali and alkali earth metallic species during pyrolysis and gasification - Zhang, Lei (Curtin University, 2015)
This study focused on the formation and transformation of nascent char structure during the pyrolysis in He and the gasification in CO2/O2 of biomass and low-rank coal. The effects of nascent char structure and the concentration of AAEM species on nascent char reactivity were investigated. The results will be useful for the development of low-emission gasification-based technologies for the utilisation of biomass and low-rank coal.